PENGARUH PENDIDIKAN DAN PELATIHAN (DIKLAT) SERTA PENEMPATAN KERJA TERHADAP KINERJA APARATUR PEMERINTAHAN DI KANTOR KEMENTERIAN AGAMA KOTA LUBUKLINGGAU - Hendra Mardiansyah; Gunadi Gunadi (Jurnal Interprof, 2018)
The purpose of this reseach is to determine how much the influenceTraining and Education (DIKLAT) program and job placement partially orsimultaneously against the performance of government officers in the ministry ofreligion on Lubuklinggau City. The sample of this study only 30 people out of 121people from all populations. The technic of data analytical uses the equation ofregression test. The result of the study find out that the outcome of multiple linearregression with the whole uses of independent variables are as follows : Y =10.894 + 0,030 X1 + 0.769 X2. From the correlation coefficient (R) theindependent variable of DIKLAT (X1) and job placement (X2) = 1.000, partiallycan be concluded have intense correlation. From the result of determinantcoefficient (R2) = 0,472, can be concluded the major percentage of officersperformance was affected by all independent DIKLAT variable (X1) and jobplacement (X2) simultantly as worth as 47,2% and 52,8% for the restaffected byother variables sush leaderships, work environment, prisoner/dicipline, andorganization culture, and etc. which is not reserached in this research. From thethree hypotheses results, the result of t test DIKLAT variable (X1) on officersperformance (Y) proves the result of Thitung = 4.990 is bigger than the value ofTtable = 1.488, with a level of significance sig. = 0.000. The result of Ttest JobPlacement variable (X2) on Officers performance (Y) proves the result of Thitung+ 6.496 is bigger than the value of Ttable = 1.234, with the level of significancessig. = 0.000. the result of F test that the value of Fhitung which obtained as12.062 > Ftable = 3.35 and the level of meaning significant simultaneously F is0.000, so can be concluded that DIKLAT (X1) and Job Placement (X2) havesignificant partially and simultantly effect to job performance from the officers onThe Ministry of Religion in Lubuklinggau city.